2013
DOI: 10.1039/c3cc40619a
|View full text |Cite
|
Sign up to set email alerts
|

Easy abstraction of a hydride anion from an alkyl C–H bond of a coordinated bis(N-heterocyclic carbene)

Abstract: The high basicity of a trimethylene-linked bis(NHC), acting as a chelating ligand in a ruthenium(0) complex, is responsible for its involvement in a room-temperature reaction in which the metal atom to which this bis(NHC) ligand is coordinated replaces a hydride anion of the ligand trimethylene linker, which can be taken by a hydride abstractor as unusual, in that role, as [Ru3(CO)12].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…Due to the ether linker in complex 3e , the OCH 2 signal pattern is simpler and appears as a well-resolved AB doublet (δ H = 4.58 and 4.53, 2 J HH = 14.4 Hz), in agreement with diastereotopic methylene protons. As noted for a ditriazolylidene rhodium complex analogous to 3d , no C–H bond activation of the linker was observed, which differs from the reactivity observed in related diimidazolylidene Rh­(III) systems …”
Section: Resultscontrasting
confidence: 55%
“…Due to the ether linker in complex 3e , the OCH 2 signal pattern is simpler and appears as a well-resolved AB doublet (δ H = 4.58 and 4.53, 2 J HH = 14.4 Hz), in agreement with diastereotopic methylene protons. As noted for a ditriazolylidene rhodium complex analogous to 3d , no C–H bond activation of the linker was observed, which differs from the reactivity observed in related diimidazolylidene Rh­(III) systems …”
Section: Resultscontrasting
confidence: 55%
“…N -Heterocyclic carbenes (NHCs) are among the most popular ancillary ligands due to a combination of unique features, such as the tunability of electronic and steric properties that influence the metal center. Moreover, the synthesis of NHC ligand precursors and the corresponding complexes is rather simple and very versatile, allowing the rational design of transition metal catalysts and the improvement of catalytic activity. Regarding the ruthenium–NHC complexes, most of the literature features ruthenium­(II) complexes, while low-valent NHC ruthenium(0) systems are restricted to a few examples based on either [Ru 3 (CO) 12 ] or [Ru­(CO) 2 (PPh 3 ) 3 ] as precursors. …”
Section: Introductionmentioning
confidence: 99%
“…Wang's group 13 has reported that, as a consequence of the high basicity of the NHC ligands, the complexes [Ru(κC-RMeIm)(CO) 4 ] (R = Ph, t Bu) are prone to undergo easy intramolecular C−H bond-activation processes that lead to cyclometalated ruthenium(II) derivatives; 14 Whittlesey's group 7 has shown that [Ru(κC-R 2 Im) 2 (CO) 3 ] (R = i Pr; R 2 Im = Et 2 ImMe 2 , i Pr 2 ImMe 2 ) complexes react easily with oxygen to give the corresponding ruthenium(II) carbonato derivatives [Ru(CO 3 )-(κC-R 2 Im) 2 (CO) 2 ]; Royo's group 12 has reported that [Fe(κC-R 2 Im)(CO) 4 ] (R = Me, Mes, 2,6-C 6 H 3 i Pr 2 ) complexes are useful catalyst precursors for the hydrosilylation of benzaldehyde; and we have recently reported the easy abstraction of a hydride anion from an alkyl C−H bond of the trimethylene- 11 We now report that the reactions of compound 1 with methyl triflate and methyl iodide selectively lead to methyl-and acetylruthenium(II) derivatives, respectively, and we complement these experimental results with theoretical DFT studies that have shed light on the mechanisms of these reactions. We chose complex 1 as a convenient stating material of the type [Ru(κC-R 2 Im) 2 (CO) 3 ] because (a) it can be easily made from [Ru 3 (CO) 12 ] and MeIm(CH 2 ) 3 ImMe (Scheme 1), 11 (b) its strong σ-donating bis(NHC) ligand enhances the nucleophilic character of its ruthenium(0) atom, 11 and (c) its chelating bis(NHC) ligand prevents the formation of mixtures containing cis and trans isomeric products, which have been observed in related ruthenium(0) complexes containing two monodentate NHC ligands. 7 It is noteworthy that no reaction of alkyl halides or pseudohalides with ruthenium(0) complexes of the type [Ru(κ 2 -L 2 )(CO) 3 ] (L 2 = chelating ligand) has been previously described, and although some reactions of methyl iodide with ruthenium(0) derivatives of the types [Ru(κP-PR 3 )(CO) 4 ], 15 trans-[Ru(κP-PR 3 ) 2 (CO) 3 ], 15 and [Ru(κ 3 P 3 -triphos)(CO) 2 ] (triphos = tridentate tripod 16 or pincer 17 P-donor ligand) have been reported, their mechanisms have not been studied by theoretical methods.…”
Section: ■ Introductionmentioning
confidence: 99%